Morpho-physiological characterization and petal color analysis of Gloriosa as a potential cut flower (Bangladesh Journal of Agriculture, 2022)
The study was conducted at Horticulture Farm, Sher-e-Bangla Agricultural University, Dhaka, during the period of January-December, 2021 to observe the morpho-physiological characteristics of Gloriosa lily with respect to growth and flowering. Thirty tubers were used in this experiment and data on morphological attributes were recorded. The colors of flowers petals were measured from three floral parts and expressed as L* (lightness), a* and b* (two Cartesian coordinates) including C* and hab (Chroma & Hue angle) based on CIE Lab scale with standard observer 100 and standard illumination D65. On the basis of flower length (7.7 cm), flower diameter (13.5 cm), leaf number per stem (26-28), flower per plant (13-15), vase life (10-12 days) explore the criteria of a cut flower and obviously this flower has the potential edition for flower industry. The study provides key indicators of Gloriosa to be a potential cut flower for which research be directed.Bangladesh J. Agri. 2019-2021, 44-46: 1-7